Witnessing Risky Behaviors in Workplaces and Predictors of Sexual Violence Awareness - Hyekyung Kang PhD, RN; Young A. Kim PhD, RN (SAGE Publishing, 2022)
To investigate the levels of witnessing risky behaviors in workplaces, such as sexual violence, and identify the factors associated with sexual violence awareness among employees. An online survey was conducted on 336 workers (aged 20-65 years), registered in an online survey company in Korea. The survey was conducted from September 15, 2021, to September 17, 2021. The participants were divided into equal quotas sampled on the basis of sex and age (participants' average age was 44 years, among whom 171 were women [50.9%] and 165 were men [49.1%]). The questionnaire contained items pertaining to demographic characteristics, gender consciousness, sexual violence awareness, witness experience, situational empathy distress, self-efficacy, and self-esteem. The collected data were analyzed using descriptive statistics, Pearson's correlation analysis, and multiple regression. Sexual violence awareness was lower among male workers than among female workers ( P  < .001), and sexual harassment and violence accounted for 54.8% of cases witnessed. The predictors of sexual violence awareness were age, gender consciousness, situational empathy, and self-esteem, with these factors explaining 53.9% of the variance. The findings highlight the need for strategies to improve sexual violence awareness and bystander intervention that are tailored to demographic predictors, such as sex, age, total length of employment, and position. These results could provide foundational data for developing sexual violence prevention education programs and practical bystander intervention programs focused on coworkers as well as promote relevant policymaking.